Mapulang Lingga: The Implementation of Yoga Tantra at the Diksa Pandita Siwa Institution in Gianyar Regency (International Journal of Interreligious and Intercultural Studies, 2024)
An ideal Pandita, is the center of vidya, an enlightened and enlightening figure. It takes a gradual and time process to become a Pandita. His spiritual ascent was an attempt to institutionalize the essence of para-aparavidya knowledge. In reality, being a Pa??ita is a "tool" to obtain gain respect and privileges in society. As a result, there is an instantiation of the d?k?? process which tends to ignore the essence; becoming a Pa??ita is only a ceremonial legality, a symbolic publication in order to be able to lead the main scale rituals in society. Based on this background, there are three research problems, namely: (1) Why is yoga tantra implemented in the Mapulang Lingga procession of the D?k?? Pa??ita ?iwa Institution in Gianyar Regency?; (2) How is the process of implementing yoga tantra in the Mapulang Lingga procession of the D?k?? Pa??ita ?iwa Institution in Gianyar Regency?; (3) What are the implications of implementing yoga tantra in the Mapulang Lingga procession of the D?k?? Pa??ita ?iwa Institution on the socio- religious life of Hindus in Gianyar Regency?. Furthermore, the data obtained are analyzed using phenomenological theory, religious theory, semiotic theory, modal theory, and reception theory, which are operationalized eclectically, based on qualitative, analytical, interpretive research methods, with a religious science approach especially yoga tantra Shivaistik approach. Implementation of yoga tantra in the mapulang lingga procession of the D?k?? Pa??ita ?iwa Institution in Gianyar Regency, or contemplative spiritual ritual practices in the form of woven supra-rational, ultra-scientific physical-metaphysical science and technology, as an attempt to unite the transcendental elements of the micro-macrocosm (atmalingga with ?iwalingga), based on two reasons, namely: first, the Theophilosophical reason, namely the attempt of Pa??ita Nabe to interpret the Kapa??it?n text so that in its functional dimension it remains relevant to the demands of the times. The second reason is the attempt to implement the catur asrama essence which are based on the panca tatwa ideology. Furthermore, the implementation process of yoga tantra in the mapulang lingga procession is reflected through five media, including: mandala (space), kala (time), yantra (equipment), mudra (priestly dance) and mantra (prayers). The implication of implementing yoga tantra in the mapulang lingga procession creates the pa??ita paripurna (full-fledged d?k??) as a representative embodiment of the unrepresentable God called "?iwa Sakala". On the other hand, for society, they have a guidelines for life when they want to realize the values of the religious teachings they believe in, at real practice in society.